ОТ ПОЭТА К ГРАЖДАНИНУ И ОБРАТНО : ХУДО ЖЕСТ ВЕНН ЫЙ ТЕ КСТ КАК ПОЛЕ ДЛ Я ЭСТЕТИ ЧЕС КОЙ РЕФЛЕ КСИИ НИ КОЛА Я НЕ КРАСО ВА - Лазутин, Всеволод (Przegląd Rusycystyczny, 2016)
FROM POET TO CITIZEN AND VICE VERSA: THE LITERARY TEXT AS THE FIELD FOR NIKOLAY NEKRASOV’S AESTHETIC REFLECTION Summary The article examines one of the key oppositions for Nikolay Nekrasov’s art: “poet vs.citizen”. Contrary to popular opinion, this opposition appears not in the Nekrasov’spoem of the same name in 1856, but much earlier, in during the publication process of his first verse book Dreams and Sounds. It appears in a critical essay on the young poet’s debut collection, which was written by journalist Vasily Mezhevich. This opposition becomes a topic of long-term thinking for Nekrasov. This reflection develops in some literary texts, where Nekrasov repeatedly simulates the situation related to the failure of his first book. The cycle of reflection completed in 1856 with a poem Poet and Citizen, in which the opposition was removed.